Track and Field Injuries: Imaging Aspects - Taneja, Atul Kumar; Djadoun, Mohamed Abdelatif; Sanfaz, Laith Anis El; Bordalo, Marcelo (Seminars in Musculoskeletal Radiology, 2025)
Track and field sports, also known as athletics, encompassing sports modalities such as running, jumping, and throwing, is a highly demanding sport with significant risk of injury. This review discusses the epidemiology, imaging techniques, and especially typical injury patterns associated with various track and field disciplines. Elite athletes, who undergo rigorous training and repetitive high-impact activities, are particularly prone to musculoskeletal injuries, with lower extremity injuries, such as muscle strains, ligament sprains, and bone stress injuries, the most common. Injury patterns vary by discipline due to specific biomechanical requirements. For instance, sprinting and jumping are more commonly linked to injuries of the foot and ankle; throwing sports often result in shoulder and elbow injuries. Advanced imaging, especially magnetic resonance imaging, plays a pivotal role in early diagnosis, allowing precise assessment of injury severity, informing prognosis, and supporting tailored treatment planning. Through detailed imaging insights and illustrations, we provide an up-to-date review on the most common injuries in track and field sports.
Keywords: summer Olympics; sports injury; sports imaging; athletics; track and field